1983
DOI: 10.1099/0022-1317-64-6-1221
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus Replication: Inhibition of Trichoplusia ni Multiple Nuclear Polyhedrosis Virus by [E]-5-(2-Bromovinyl)-2'-deoxyuridine

Abstract: SUMMARY[E]-5-(2-bromovinyl)-2'-deoxyuridine (BVdU) inhibits the replication of the baculovirus Trichoplusia ni multiple nucleocapsid nuclear polyhedrosis virus in Spodoptera frugiperda cells. Virus-specific DNA synthesis and late protein synthesis are suppressed by the drug. BVdU is phosphorylated by deoxythymidine (deoxycytidine) kinase present in both uninfected and virus-infected cells, and in its 5'-triphosphate form it inhibits DNA polymerase activity in virus-infected cells. The effect of the BVdU is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a previous study on the effect of BVdU on baculovirus replication (Wang et al, 1983) it was shown that both BVdU and its triphosphorylated derivative inhibited DNA polymerase activity in crude cell extracts, and the direct effect of BVdU on DNA polymerase activity was attributed to its phosphorylation by cell or viral deoxypyrimidine kinases present in the extract. By analogy with certain herpesviruses, only BVdU triphosphate should block DNA polymerase activity (De Clercq et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study on the effect of BVdU on baculovirus replication (Wang et al, 1983) it was shown that both BVdU and its triphosphorylated derivative inhibited DNA polymerase activity in crude cell extracts, and the direct effect of BVdU on DNA polymerase activity was attributed to its phosphorylation by cell or viral deoxypyrimidine kinases present in the extract. By analogy with certain herpesviruses, only BVdU triphosphate should block DNA polymerase activity (De Clercq et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Aphidicolin, BVdU and BVdU triphosphate have been shown to inhibit both cell and virus-stimulated enzymes in crude and partially purified preparations (Miller et al, 1981;Wang et al, 1983). BVdU and aphidicolin both inhibit baculovirus replication (Wang et al, 1983;X.…”
Section: Identification Of Dna Polymerasementioning
confidence: 99%
See 2 more Smart Citations
“…This class of compounds targets DNApol by mimicking and/or competing with the normal deoxynucleoside triphosphate (dNTP) substrates. Several inhibitors of baculovirus DNA replication have been documented, with the majority falling within this category, including, surprisingly, the antiretroviral drug abacavir (26,43,51). Of these, the effects of abacavir and aphidicolin on AcMNPV replication were reversible (43).…”
mentioning
confidence: 99%